Beyond the buzz: analyzing actors promoting regenerative agriculture in Europe - Schreefel, Loekie; Steenman, Emile; Adler, Fabian; Buffara, Ricardo; Freundt, Stephan; Declerck, Fabrice; Duncan, Jessica; Giller, Ken E.; Koster, Howard; van Zanten, Hannah H. E. (2025)
Regenerative agriculture is advocated as a response to environmental and socio-economic challenges, yet little research systematically examines its key proponents. We analyzed 849 actor websites and interviewed 131 regenerative farmers across five European countries. We mapped actor types, locations, sizes, and promoted themes (e.g. biodiversity) and practices (e.g. no-tillage). Our findings suggest regenerative agriculture originated as a grassroots approach to farming that was co-opted by non-farming actors around 2020. Since 2021, the number of new regenerative farmers declined, raising concerns that the focus shifted from farming to marketing driven by multinational companies. Policy engagement was limited, and actors were mainly urban-based (e.g. NGOs). The most promoted themes were soil health and biodiversity. Among nearly 5000 cited practices, cover cropping and crop diversification dominated. We argue that the burden of proof for regenerative agriculture to be sustainable lies in its ability to regenerate the environment—until then, its impact remains uncertain.